Предмет:
МатематикаАвтор:
аноним1) (а + 1) * (а + 1) * (а + 1) = (a2 + а + а +1) * (а + 1) = (a2 + 2 * а +1) * (а + 1) = a3 + 2 * a2 + а + a2 + 2 * а +1 = a3 + 3 * a2 + 3 * а +1;
2) (а + в) * (а - в) * (а + в) = (a2 - a * b + a * b - b2) * (a + b) = (a3 + a2 * b - a2 * b -a *b2 + a2 * b + a * b2 - a * b2 - b3) = a3 + a2 * b -a2 * b - a * b2 + a2 * b + a * b2 - a * b2 - b3 = – a * b2 + a2 * b + a3 – b3;
3) (а + в + с) * (а + 1) = = (a2 + a + a * b + b + a * c + c) = a2 + a + a * b + b + a * c + c = a * b + a * c + a2 + a + b + c;
4) (x + 1) * (x2 - x + 1) = (x3 - x2 + x + x2 - x + 1) = x3 - x2 + x + x2 - x + 1 = x3 + 1;
5) (x3 + 2 * x - 3) * (2 - 3 * x) = (2 * x3 - 3 * x4 + 4 * x - 6 * x2 - 6 + 9 * x) = 2 * x3 - 3 * x4 + 4 * x - 6 * x2 - 6 + 9 * x = – 3 * x4 + 2 * x3 – 6 * x2 + 13 * x – 6.
Автор:
maximilian88Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть